Culture and Community in Agri-Tourism: Contributions of Cultural and Creative Resources to Strawberry Tourism - Suryani, Adi; Soedarso, Soedarso; Muhibbin, Zainul; Saifulloh, Moh.; Nisa, Khairun (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Agritourism is currently thriving as many modern visitors favor returning to rural nature over visiting metropolitan destinations. This evolving tendency might stoke locals' enthusiasm to start and develop agri-based tourism by using their farms, gardens, and other physical natural assets for both primary and secondary employment, such as by opening their properties up as agri-tourism destinations. These activities may improve the local population's ability to support themselves and their well-being as tourism has the potential to have multiplier effects. The growth of agritourism, however, might not be entirely dependent on a destination's natural or environmental resources. By using its cultural potential, it can instead be strengthened. The purpose of the research is to investigate how culture and community creativity can improve agritourism. The study is carried out at Lumbung Strawberry Tourism in Batu, Malang. The study finds that culture, when combined with natural resources, may support the growth of agritourism by enhancing the ethno-authenticity of the destination, highlighting its distinctiveness, communicating it, fostering locals' creativity, fostering innovation, boosting its popularity, and facilitating marketing. Along with utilizing its local rural agriculture, Lumbung Strawberry embraces the current of digital culture by creating destination Instagram accounts and offering locations for taking selfies and pictures.